Studies of the influences of different N fertilizers and Microbion UNC bacterial fertilizer on the nutrient content of soil - Balla Kovács, Andrea; Szabó, Anita; Bartáné Szabó, Emese (Acta Agraria Debreceniensis, 2010)
A field experiment was conducted to examine the effects of different nitrogen fertilizers in combination with bacterial fertilizer onnutrient uptake of horseradish and plant available nutrients of the soil. Three different N fertilizers, ammonium-nitrate, urea and calciumnitrate(116 kg ha-1 N) in combination with Microbion UNC bacterial fertilizer (2 kg ha-1) were applied as treatments in a randomizedcomplete block design in three replications. In this paper we presented the results of soil measurements. The soil of the experimental areawas chernozem with medium sufficiency level of N and P and poor level of K.Our main results:The amount of 0.01M CaCl2 soluble inorganic nitrogen fractions, NO3--N and NH4+-N and also the quantity of soluble organic-N werealmost the same in the soil. N fertilizers significantly increased all the soluble N fractions. The amount of NO3--N increased to the greatestextent and the increase of organic N was the slightest. We measured the largest CaCl2 soluble NO3- -N and total-N contents in the plotstreated with ammonium-nitrate, the largest NH4+-N in the plots treated with calcium-nitrate and the largest organic-N fraction in plotstreated with urea.Bacterial inoculation also increased both soluble inorganic nitrogen forms and also total-N content of soil compared to the control. Inthe case of combined (artificial and bacterial fertilizer) treatments we measured lower NO3--N, organic-N and total-N compared to thevalues of plots having only nitrogen fertilizer treatments. On the contrary in the plots with combined treatments the CaCl2 soluble NH4+-Ncontent of soil in more cases were higher than that of values with artificial fertilizer treatment.As a function of calcium-nitrate application increased AL-P2O5 and AL-K2O values were measured compared to control. MicrobionUNC supplement of calcium nitrate yielded also increase in AL-P2O5 and AL-K2O values, till then supplement of ammonium-nitrate fertilizeryielded a decrease in these values compared to the control.All nitrogen fertilizers resulted in a significant decrease in AL-Mg content of soil compared to the control. Nevertheless bacterialfertilizer increased AL-Mg values in any cases.